The Heart of Teaching: Can Empathy-Focused CPD Elevate Tutoring? - Ang, Ching Ting; Dewitt, Dorothy (Journal of Research, Innovation, and Strategies for Education (RISE), 2025)
This study aims to explore how a Continuous Professional Development (CPD) programme focused on empathy-based pedagogy can influence the teaching practices of private tutors, with a particular focus on enhancing social-emotional learning (SEL) and student well-being. Given the critical role private tutors play in the academic and emotional development of students, the research seeks to fill the gap in professional development opportunities that support empathy-driven teaching approaches. The methodology used for this qualitative case study includes semi-structured interviews, participant observation, and reflective journaling to collect data on how private tutors perceive and implement empathy-based strategies. The study was conducted at a private tutoring centre, with a focus on understanding the challenges tutors face when applying empathy-based pedagogy and how these strategies impact student engagement and interactions. The findings suggest that empathy-based CPD has a transformative effect on tutors' teaching practices. It enhances their ability to foster stronger student-teacher relationships, create more supportive learning environments, and improve student engagement. Tutors reported that the programme helped them develop greater emotional awareness and communication skills, which in turn positively influenced their students' academic and social development. However, the research is limited by its focus on a single tutoring centre, which may affect the generalisability of the findings to other contexts. Additionally, the study’s reliance on qualitative data means that further quantitative research could be beneficial to corroborate the results.